Outcomes with intravascular ultrasound-guided stent implantation: a meta-analysis of randomized trials in the era of drug-eluting stents - Kang, Soo-Jin; Mintz, Gary S. (Journal of Thoracic Disease, 2016)
Intravascular ultrasound (IVUS) is a useful tool for planning percutaneous coronary intervention (PCI) by informing the operators of lesion severity, reference vessel size, lesion length, and extent of calcification. With validated criteria for stent underexpansion and edge problems, post-stenting IVUS has been used to optimize stent deployment to prevent stent failure (restenosis and early thrombosis). Despite its potential benefits, routine use of IVUS has been restricted by cost and time and questions regarding clinical data. In reality IVUS is used in less than 20% of all PCIs cases in the United States (1).